Effectiveness of Povidone-Iodine 1% Eye Drop on Streptococcus pneumoniae and Escherichia coli Induced-Keratitis in Mice: - Hadipour Jahromy, Mahsa; Najafi, Abdolhamid; Majdi Nassab, Farzaneh; Moiniyan, Mahya (Galen Medical Journal, 2019)
Background: Bacterial keratitis is an ophthalmic infection that may result in irreversible corneal damage. This study aimed to examine the effectiveness of povidone-iodine eye drop 1% in eye infection caused by inoculation of Streptococcus pneumoniae and Escherichia coli of mice. Materials and Methods: In this study, 49 adult male CBA/J mice were used that divided into seven equal groups. The corneas of all mice were scratched and infected with a clinical strain of either S. pneumoniae or E. coli topically, except control group. Subgroups received chloramphenicol 0.5% eye drop twice daily in case of S. pneumoniae infection or ciprofloxacin 0.3% eye drop every 4 hours following E. coli infection from or povidone-iodine 1% eye drop in both groups, from post infection (PI) day 3 to7. Slit lamp examinations (SLE) of the corneas and eyes were performed every day to examine detectable or intense corneal opacity and erosion. Results: In all infected mice, SLE scores were significantly higher than the control group on PI day 3. Scores increased steadily by time in all infected groups without treatment, reached to maximal value on PI day 7. In infected groups, treatment with either povidone-iodine 1% or chloramphenicol 0.5% or ciprofloxacin 0.3% on day 3, significantly decreased the SLE scores on PI day 7. Conclusion: Povidone-Iodine 1% was effective to decrease S. pneumoniae and E. coli induced-keratitis symptoms in mice. Treatment with povidone-iodine 1% was observed time-dependently and was comparable to common eye drop antibiotics. [GMJ.2019;8:e1161]